Loss of the AE3 Cl−/HCO−3 exchanger in mice affects rate-dependent inotropy and stress-related AKT signaling in heart - Prasad, Vikram; Lorenz, John N.; Lasko, Valerie M.; Nieman, Michelle L.; Al Moamen, Nabeel J.; Shull, Gary E. (Frontiers in Physiology, 2013)
Cl−/HCO−3 exchangers are expressed abundantly in cardiac muscle, suggesting that HCO−3 extrusion serves an important function in heart. Mice lacking Anion Exchanger Isoform 3 (AE3), a major cardiac Cl−/HCO−3 exchanger, appear healthy, but loss of AE3 causes decompensation in a hypertrophic cardiomyopathy (HCM) model. Using intra-ventricular pressure analysis, in vivo pacing, and molecular studies we identified physiological and biochemical changes caused by loss of AE3 that may contribute to decompensation in HCM. AE3-null mice had normal cardiac contractility under basal conditions and after β-adrenergic stimulation, but pacing of hearts revealed that frequency-dependent inotropy was blunted, suggesting that AE3-mediated HCO−3 extrusion is required for a robust force-frequency response (FFR) during acute biomechanical stress in vivo. Modest changes in expression of proteins that affect Ca2+-handling were observed, but Ca2+-transient analysis of AE3-null myocytes showed normal twitch-amplitude and Ca2+-clearance. Phosphorylation and expression of several proteins implicated in HCM and FFR, including phospholamban (PLN), myosin binding protein C, and troponin I were not altered in hearts of paced AE3-null mice; however, phosphorylation of Akt, which plays a central role in mechanosensory signaling, was significantly higher in paced AE3-null hearts than in wild-type controls and phosphorylation of AMPK, which is affected by Akt and is involved in energy metabolism and some cases of HCM, was reduced. These data show loss of AE3 leads to impaired rate-dependent inotropy, appears to affect mechanical stress-responsive signaling, and reduces activation of AMPK, which may contribute to decompensation in heart failure.